Implementasi Model Pembelajaran Quantum Learning Untuk Meningkatkan Hasil Belajar Pendidikan Agama Katolik Siswa Kelas V SD Inpres Bhoanawa 1 - Thomasine Sofia Siganono (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
The purpose of this study was to determine the application of the quantum learning model and improve learning outcomes of Catholic Religion education for fifth grade students of SD Inpres Bhoanawa 1. This study used a qualitative approach with the type of classroom action research. The results of this study indicate an increase in science learning outcomes with the application of the quantum learning model. This shows that the quantum learning model can improve student learning outcomes in the fifth grade Catholic Religious Education subject in SD Inpres Bhoanawa 1.